Optimasi Pengaruh Motivasi, Kompetensi, dan Budaya Organisasi Terhadap Kinerja Karyawan - Tubagus Naizak Sis Herlambang; Christian Wiradendi Wolor; Marsofiyati Marsofiyati (Epsilon Journal of Management, 2024)
This study aims to analyze the influence of motivation, competence, and organizational culture on employee performance. The research design used in this study is a quantitative method with descriptive analysis. Data collection was conducted online using a questionnaire with a Likert scale ranging from one to five and obtained through simple random sampling from 86 respondents who are over 17 years old and have worked or are currently working in an organization or company. The data analysis techniques used in this study include: Outer Model analysis with calculations for Convergent Reliability, Discriminant Validity, Composite Reliability, Cronbach's Alpha, and Inner Model analysis with calculations for t-statistic, R-Square, f-Square, and VIF using the smartPLS (Partial Least Square) version 4.0.9.3 software. The results of this study indicate that: 1.) Motivation has a significant influence on employee performance. 2.) Competence has a significant influence on employee performance. 3.) Organizational culture has a significant influence on employee performance.